Inflammatory Myofibroblastic Tumor of the Liver Mimicking Metastasis on 18F-FDG PET/CT. (January 2021) - Raad, Roy A.; Haddad, Laura; Jabbour, Teddy; El-Rassi, Ziad
Abstract : Abstract: A 62-year-old woman with history of stage III endometrial cancer was found to have a small enhancing liver lesion on follow-up abdominal CT and MRI, suspicious for metastasis. Subsequent 18 F-FDG PET/CT was performed, demonstrating intense uptake within the liver lesion, consistent with metastasis. Subsequently, laparoscopic wedge liver lesion resection was performed. Histopathologic examination confirmed the diagnosis of inflammatory myofibroblastic tumor (IMT) with predominant inflammatory cells. Although solitary liver IMTs are rare occurrences with imaging features overlapping with malignancy, IMT should be considered in the differential diagnosis of suspicious liver lesions, especially when the pattern of spread is unusual.